The Trend of Children Mortality Rates in Indonesia - Sani Rachman Soleman (Faculty of Public Health, Sriwijaya University, 2020)
Children mortality rates describe the health services' quality as indicators of each countries' welfare, particularly in Indonesia. Several factors were determined as the main contributors of mortality, such as neonatal factors, maternal, environment and health services. The important of this research is to give recommendation to the government of Indonesia to propose some policies in handling of the increasing children mortality and modifying underlying disease as contributor mortality among children in Indonesia. The design of this study is cross sectional. The data was taken from World Health Organization Maternal Child Epidemiology Estimation from 2000 to 2017. There were three main categories : neonatal mortality rate (NND), post neonatal mortality rate (PND) and under five mortality rate (UFIVE). The leading causes of mortality were searched according to those categories and followed by descriptive analysis by line graphs. According to the data that had been found, there was declining on NND (102.700 to 60.986), PND (138.553 to 63.471), UFIVE (241.253 to 124.457). The children mortality tend to decline at the range of 17 years, meanwhile the highest mortality among the three of groups are : premature birth in neonates, ARI in post neonates and premature birth in under five children. In conclusion, the trend of three parameters of children mortality declined within 17 years. On several cases, there were outbreak of injury on 2004 and fluctuation of measles incident among infant and under five children. Premature birth and ARI have the highest prevalence among children in Indonesia.